2005
DOI: 10.1021/es0481124
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Organochlorine Differences between Arctic Regions Vary among Trophic Levels?

Abstract: Statistical analysis of organochlorine contaminants (OCs) in marine mammals has shown that, for most OCs, the European Arctic is more contaminated than the Canadian and U.S. Arctic. Recently, comparison of OC concentration ranges in seabirds, arctic cod (Boregadus saida), and zooplankton, found no difference between these regions. To address these inconsistencies, marine food web OC data from the European (central Barents Sea (CBS)) and Canadian Arctic (Northwater Polynya (NOW)) were simultaneously statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 40 publications
0
3
1
Order By: Relevance
“…In Kongsfjorden, the contribution of local point sources on PCB concentration in macrobenthos has been shown to be minimal or non-existent (Hop et al, 2001). The findings of similar P CHLOR levels in amphipods from the European and North American Arctic (Borgå et al, 2005), however, are contradictive to the spatial pattern found between the study of Fisk et al (2003) and our results. The trend of lower P CHLOR levels in bivalves from the European than the North American Arctic (Fisk et al, 2003) has been confirmed by other studies done in Svalbard (Angot, 2009;Tessmann, 2008).…”
Section: Oc Patterns In Arctic Bivalvescontrasting
confidence: 99%
See 1 more Smart Citation
“…In Kongsfjorden, the contribution of local point sources on PCB concentration in macrobenthos has been shown to be minimal or non-existent (Hop et al, 2001). The findings of similar P CHLOR levels in amphipods from the European and North American Arctic (Borgå et al, 2005), however, are contradictive to the spatial pattern found between the study of Fisk et al (2003) and our results. The trend of lower P CHLOR levels in bivalves from the European than the North American Arctic (Fisk et al, 2003) has been confirmed by other studies done in Svalbard (Angot, 2009;Tessmann, 2008).…”
Section: Oc Patterns In Arctic Bivalvescontrasting
confidence: 99%
“…This percentage is estimated based on the PCB pattern observed before in M. truncata from Svalbard (Hop et al, 2001). A recent comparison of circumpolar OC data also showed higher P PCB in amphipods from the North American compared to the European Arctic (Borgå et al, 2005). Fisk et al (2003) suggested that elevated PCB levels might be due to local input from point sources in the North American Arctic.…”
Section: Oc Patterns In Arctic Bivalvesmentioning
confidence: 89%
“…Therefore, in order for similar steady-state EFs to occur between these two populations, the birds must have a regular consumption of prey containing analogous enantiomer distributions of chiral compounds. It has been shown that glaucous gulls from Svalbard and the NOW polynya in the Canadian Arctic feed at similar trophic levels , although their opportunistic diets may include a wide variety of food items that may differ between these two populations. In general, the few studies investigating EFs in lower trophic level organisms from both Svalbard and the NOW polynya found that they contained EFs of most OC compounds which were closer to racemic than EFs measured in glaucous gulls from these arctic locations ,− .…”
Section: Resultsmentioning
confidence: 99%
“…Environmental changes in contaminant exposure appear to be reflected faster in zooplankton than in longer-lived, higher trophic-level organisms. 92 Thus, extrapolating the results of this study to approximate future climate change effects should be done with caution. Space-for-time approaches require two contrasting sites that are comparable with regards to other potential confounding factors within- or between-sites.…”
Section: How Do Physical Environmental Changes Affect Pop Exposure In...mentioning
confidence: 96%